(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
For university students, the educational environment is not only a place for acquiring academic knowledge but also a space for personal development and self-formation. One of the critical factors in this process is the formation of interpersonal relationships within the group. Through interpersonal interactions, students develop social connections, receive psychological support, and strengthen mutual trust. The willingness to harmonize opinions, the formation of constructive approaches in conflicts, and the overall psychological characteristics and influence mechanisms are central themes of this research. These aspects are analyzed in relation to educational tasks and the structure of interpersonal communication skills.